Generalisasi Bilangan Kromatik Pada Beberapa Kelas Graf Korona - Riduan Yusuf; Fitria Puspa Dewi; Firmansyah; Abdul Mujib (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
For example is a chromatic number with the smallest integer so that the graph has a true vertex coloring with k color. Chromatic number is still an interesting study which is still being studied for its development through graph coloring. Graph coloring is a special case of graph labeling. Labeling here means, giving color to the points at a certain limit so that no two vertices have the same color. This study aims to calculate the chromatic number in several classes of graphs including , , Based on the results of the study, generalization of the chromatic number of the graph class . Class and for class for even n and 4 for odd n. Keywords: graph, graph coloring, chromatic number For example is a chromatic number with the smallest integer so that the graph has a true vertex coloring with k color. Chromatic number is still an interesting study which is still being studied for its development through graph coloring. Graph coloring is a special case of graph labeling. Labeling here means, giving color to the points at a certain limit so that no two vertices have the same color. This study aims to calculate the chromatic number in several classes of graphs including , , Based on the results of the study, generalization of the chromatic number of the graph class . Class and for class for even n and 4 for odd n. Keywords: graph, graph coloring, chromatic number